2009
DOI: 10.1007/s10562-009-9973-3
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affect on the Reaction Performance of the Oxidative Dehydrogenation of n-Butene to 1,3-Butadiene Over Zn-Ferrite Catalysts

Abstract: Two types of zinc ferrite catalysts have been prepared by physical mixing or coprecipitation and applied to the oxidative dehydrogenation of n-butene to 1,3-butadiene. It is observed that the catalytic activity is significantly dependent upon not only the crystallinity but also the composition of a ferrite catalyst. If crystallinity of a catalyst is too high, the oxygen spillover through the lattice is severely suppressed and results in low catalytic activity. On the other hand, the presence of a-Fe 2 O 3 in f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The change in the EPR spectra (Supplementary data) was also consistent with an increase in particle size for all the ferrites. Surprisingly the BET surface area of ferrite catalysts is rarely reported in the literature and even then only pre-reaction [2], so there is little data in the literature to compare with our data. Nevertheless, these are significant losses in surface area, which are due to the presence of steam in the feed [14], yet the loss in area is not reflected in any equivalent loss of activity indicating no direct link between surface area and activity [5].…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…The change in the EPR spectra (Supplementary data) was also consistent with an increase in particle size for all the ferrites. Surprisingly the BET surface area of ferrite catalysts is rarely reported in the literature and even then only pre-reaction [2], so there is little data in the literature to compare with our data. Nevertheless, these are significant losses in surface area, which are due to the presence of steam in the feed [14], yet the loss in area is not reflected in any equivalent loss of activity indicating no direct link between surface area and activity [5].…”
Section: Discussionmentioning
confidence: 74%
“…Nanocrystalline ferrites give unique characterisation fingerprints and from the initial characterisation by AAS, XRD, Raman spectroscopy and EPR it is clear that nanocrystallites of the five ferrites were produced. The XRD revealed that the catalysts were not highly crystalline, which is an important parameter as a lack of highly crystalline material has been shown to be a key factor in the production of an active catalyst [2], as a highly crystalline form inhibits oxygen mobility. XPS revealed that the surface Fe:A 2+ ratio of the ferrites did not match the bulk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation